Manufacturing method of treatment material and treatment material
Patent Information
- Application Number
- JP2023130179
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
AI Technical Summary
【0010】 本発明によれば、小さい工数で応力腐食割れに対する耐性を高めることができる処理材の製造方法および処理材を提供することができる。 上記した以外の課題、構成及び効果は、以下の実施形態の説明により明らかにされる。
Smart Images

Figure 2025025433000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a treatment material and the treatment material. [Background technology]
[0002] As the speed of high-speed railway vehicles, such as the Shinkansen (registered trademark), increases, weight reduction of the vehicles is being promoted. Instead of the steel materials conventionally used in vehicle structures, the use of aluminum alloys, which have excellent light weight properties, has been considered. For example, aluminum alloys are used for the entire vehicle structure of the 200 series Shinkansen and later trains.
[0003] Aluminum alloys (e.g., 6000 series) have the advantage that they are easy to process, including extrudability, and that their properties can be adjusted by heat treatment. However, they also have the disadvantage that they are generally more difficult to weld than iron materials, due to their high thermal conductivity and the need to remove the oxide film that forms on the aluminum alloy surface when welding.
[0004] For this reason, since the year 2000, friction stir welding (FSW), which involves pressing a rotating tool into the butt joint of the parts to be joined and moving the rotating tool along the weld line, has been used to manufacture large structures such as railway car bodies (see Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-090655 Summary of the Invention [Problem to be solved by the invention]
[0006] Among the structural materials constituting large aluminum alloy structures, high-strength aluminum alloys (e.g., 7000 series) are sometimes used as structural materials or reinforcing members in locations bearing high loads. Since 7000 series aluminum alloys have excellent static strength and fatigue strength, they can achieve a significant weight reduction effect when used as structural materials or reinforcing members, but they are required to be designed and post-processed with consideration given to stress corrosion cracking (SCC).
[0007] An object of the present invention is to provide a method for producing a treated material, which can increase resistance to stress corrosion cracking with a small number of steps, and the treated material. [Means for solving the problem]
[0008] In order to solve the above problems, one of the representative methods for producing the treatment material of the present invention is as follows: A first step of performing friction stirring processing on a material to form a stirring portion; A second step of cutting out a treatment material from the material along the stirring portion; This is achieved by having:
[0009] One representative treatment material of the present invention is: A treatment material having a central portion and a peripheral portion continuous with the central portion, the treatment material being made of the same material, The central portion has a structure in which crystal grains are arranged in layers, the structure of the peripheral portion is more finely recrystallized than the structure of the central portion; This is achieved by exposing the finely crystallized structure at the outer edge of the treatment material. Effect of the Invention
[0010] According to the present invention, it is possible to provide a manufacturing method of a treatment material and a treatment material that can increase resistance to stress corrosion cracking with a small number of steps. Problems, configurations and effects other than those described above will become apparent from the following description of the embodiments. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic diagram showing how a tool is inserted into a material and moved along a marking line drawn on the material. [Diagram 2] FIG. 2(a) is a schematic diagram of a funnel-type tool, and FIG. 2(b) is a schematic diagram of a shoulderless-type tool. [Diagram 3] FIG. 3 is a schematic diagram showing a state in which a tool is inserted into one surface of the material and a stir portion is formed in the material along the marking line. [Figure 4] Figure 4(a) is a cross-sectional macrostructure image of the stirring area where material was stirred with a funnel-type tool, and Figure 4(b) is a cross-sectional macrostructure image of the stirring area where material was stirred with a shoulderless tool. [Diagram 5] Figure 5(a) is an IPF map of the stirring area using a funnel-type tool, Figure 5(b) is an IPF map of the stirring area using a shoulderless tool, and Figure 5(c) is an IPF map of the material (base material). [Figure 6] FIG. 6 is a cross-sectional view (corresponding to the cross-sectional view of FIG. 2A-A) of a material in which one stirring section formed by inserting a tool from one side of the material is overlapped with the other stirring section formed by inserting a tool from the other side. [Figure 7] FIG. 7 is a perspective view of the treatment material cut out along the stirring portion formed along the marking line. [Figure 8] FIG. 8 is a schematic diagram of a cross section of a treatment material cut along a stirring portion formed along the marking line, the cross section intersecting the marking line. [Figure 9] FIG. 9 is a schematic diagram showing an example in which a treatment material manufactured by the manufacturing method according to this embodiment is welded to a fastening portion between an underframe of a railway vehicle and a yaw damper support portion for reinforcement. [Figure 10] FIG. 10 is a schematic diagram showing the treatment material welded to the railway car (an enlarged view of part A in FIG. 9). [Figure 11] FIG. 11 is a cross-sectional view of a portion reinforced with a treated material, taken along a line intersecting the longitudinal direction of the railway car. [Figure 12]FIG. 12 is a flow chart showing a method for producing a treatment material according to this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, a manufacturing method of a treated material using a material according to the present invention and an embodiment related to the treated material will be described with reference to the drawings. Here, the material is a material (base material, material, member) obtained by a rolling or extrusion molding process, and the treated material is obtained by cutting the material into a predetermined shape after FSW processing described later.
[0013] First, we define each direction to explain the manufacturing method of the treatment material. The longitudinal direction of the material is the x-direction, the short-side direction of the treatment material on the same plane as the x-direction is the y-direction, and the thickness direction of the treatment material is the z-direction. Hereinafter, these directions may be simply referred to as the x-direction, y-direction, and z-direction.
[0014] Here, the directions are defined when the raw material is a rolled material. The roll direction when rolling the raw material is either the x direction or the y direction of the xy plane. In other words, the direction perpendicular to the roll when rolling the raw material coincides with the z direction. Next, the directions are defined when the raw material is an extruded material. The extrusion direction when extruding an extruded material is not particularly limited to the x, y, or z directions.
[0015] Fig. 1 is a schematic diagram showing how the tool is inserted into the material and moved along the marking line drawn on the material, Fig. 2(a) is a schematic diagram of a funnel-type tool, Fig. 2(b) is a schematic diagram of a shoulderless-type tool, and Fig. 3 is a schematic diagram showing the state in which the tool is inserted into one side of the material and a stirring portion is formed in the material along the marking line.
[0016] An aluminum alloy raw material (base material) 20 having a predetermined plate thickness t is prepared, and a scribe line 22 of a treatment material 24 to be cut out from the raw material 20 is marked on the raw material 20. The scribe line 22 may be actually marked on one side of the raw material 20, or may be virtually represented by coordinate data on the xy plane corresponding to the scribe line 22.
[0017] In general, the tool 10 has a cylindrical large diameter portion 10a and a small diameter portion 10b provided coaxially with the large diameter portion 10a and continuous with the end portion in the z direction. The small diameter portion 10b indicates a portion having a smaller radius than the radius of the cylindrical large diameter portion 10a, and the small diameter portion 10b does not necessarily have to be cylindrical. A screw or the like (right-handed or left-handed screw, any pitch) may be machined on the cylindrical surface of the small diameter portion 10b so that the tool 10 can be pressed against the material (base material portion) 20 to efficiently stir the material 20.
[0018] The tool 10 is pressed against the material 20 in the -z direction while rotating at a predetermined rotation speed, and then the tool 10, rotating at the predetermined rotation speed, is moved at a predetermined moving speed in the xy plane along the marking line 22 to stir a part of the material 20. This series of operations is sometimes called FSW (Friction Stir Welding) processing.
[0019] The form of the tool 10 may be a funnel-type form having a large diameter portion 10a, a shoulder portion 10c provided at the lower end of the large diameter portion 10a, and a small diameter portion 10b extending downward from the lower end of the shoulder portion 10c, as shown in FIG. 2(a), or may be a shoulderless form having a large diameter portion 10a and a small diameter portion 10b in a truncated cone shape whose radius gradually decreases continuously from the lower end surface of the large diameter portion 10a, as shown in FIG. 2(b).
[0020] The function of the tool 10 is to subject a part of the material to FSW processing to produce a treated material, that is, to stir and finely recrystallize the structure of a part of the material with the tool 10. Therefore, any tool capable of stirring a part of the material 20 may be used, and is not limited to the funnel-type tool and shoulderless-type tool described above, but may be any tool capable of stirring a part of the material 20, such as a bobbin-type tool.
[0021] Taking the funnel-type tool 10 as an example, the process of machining the stirring portion 26a (26b) by FSW processing on the material 20 will be described. The funnel-type tool 10 is attached to a CNC (Computerized NC) machine tool or the like having a computer numerical control function that uses numerical information to command the work steps required to form the stirring portion 26a (described later) along a marking line 22 drawn on the xy plane of the material 20.
[0022] A CNC machine tool (not shown) rotates the tool 10 in a rotation direction 100 at a rotation speed of about 500 to 3000 rpm, while pressing the tip of the small diameter portion 10b of the funnel-type tool 10 against one surface 20a of the blank 20 to insert it into the blank, and then lowers the tip along a vertical movement direction 101 until it reaches the vicinity of the other surface 20b of the blank 20. At this time, it is desirable that the shoulder portion 10c of the funnel-type tool 10 (the boundary between the small diameter portion 10b and the large diameter portion 10a) abuts against one surface 20a of the blank 20.
[0023] Furthermore, the CNC machine tool moves the funnel-shaped tool 10 on the xy plane while the shoulder portion 10 c of the funnel-shaped tool 10 is in contact with one surface 20 a of the blank 20 , forming a stirring portion 26 a in the blank 20 along the marking line 22 .
[0024] Although not described in detail, after the process of forming the stirring portion 26a with the funnel-shaped tool 10 is completed, when the funnel-shaped tool 10 is pulled up from the stirring portion 26a, a hole formed by the small diameter portion 10b of the funnel-shaped tool 10 remains in the stirring portion 26a. Therefore, after determining the shape of the material to be cut out (corresponding to the scribe line 22), the tool 10 is moved to the portion of the material 20 to be removed in the subsequent process (outside the area surrounded by the scribe line 22), and the scribe line 22 (tool movement path 102) of the tool 10 is determined so that the funnel-shaped tool 10 can be pulled out at this portion.
[0025] Figure 4(a) is a cross-sectional macro-structure image of the stirring area where the material was stirred with a funnel-type tool, and Figure 4(b) is a cross-sectional macro-structure image of the stirring area where the material was stirred with a shoulderless tool. Figure 5(a) is an IPF map of the stirring area with the funnel-type tool, Figure 5(b) is an IPF map of the stirring area with the shoulderless tool, and Figure 5(c) is an IPF map of the material (base material).
[0026] An IPF map (inverse pole figure crystal orientation map) is a map that uses an inverse pole figure color key to show the normal orientation of the crystal plane at each measurement point that is parallel to the indicated surface on the sample, and is most often used to display data from the EBSD method, allowing the distribution of crystal orientations to be understood by the color. However, in Figure 5, it is shown as a monochrome image.
[0027] The cross-sectional macrostructure images shown in Figures 4(a) and (b) were obtained by taking macroscopic photographs of a cross section cut from a 6 mm-thick test piece cut from a 7000 series aluminum alloy (Al-Zn-Mg aluminum alloy), which is highly susceptible to stress corrosion cracking, along the direction (LT(y) direction) intersecting the rolling direction (L(x) direction), after FSW processing has been performed. The cross section was then cut in a vertical cross section (L(x)-ST(z) plane) parallel to the rolling direction (L(x) direction).
[0028] 4, the structure of the material 20 is a pancake-like structure in which crystal grains are arranged in layers in the rolling direction, whereas the structure of the stir portion 26a FSWed with the funnel-type tool 10 and the shoulderless-type tool 10 is modified into a fine recrystallized structure by plastic flow (stirring) of the material 20 by the tool 10, and is modified into a structure with high resistance to stress corrosion cracking. That is, by observing the cross-sectional macro-structure image of the processed material, it can be seen that the stir portion is modified into a fine recrystallized structure compared to the other parts (center part). The fine recrystallized structure is preferably a structure in which the observed crystal grain size is 1 μm or more and 30 μm or less, preferably 5 μm or more and 20 μm or less.
[0029] The IPF maps in Figures 5(a) and 5(b) were obtained by observing the grain size of the stir portion 26a by electron backscattered diffraction pattern (EBSD) on the cut surface including the stir portion 26a after horizontally cutting the test pieces that were FSWed with a funnel-type tool and a shoulderless tool at the half-thickness position. Also, Figure 5(c) is a result of observing the grain size by EBSD on the test piece (material 20) that was not FSWed after horizontally cutting it at the half-thickness position.
[0030] As shown in Fig. 5(c), it is observed that the structure of the stir zone 26a FSWed with the funnel-type tool 10 in Fig. 5(a) has been modified to an equiaxed fine recrystallized structure with a crystal grain size of 10 to 20 μm or less, compared to the structure of the raw material 20 in which elongated crystal grains are arranged in layers. Furthermore, it is observed that the structure of the stir zone 26a FSWed with the shoulderless tool 10 in Fig. 5(b) has been modified to a fine recrystallized structure with a crystal grain size of 5 to 10 μm or less, which is less than half the grain size of the grains FSWed with the funnel-type tool 10.
[0031] The inventors also prepared samples cut to a thickness of 100 nm or less from the raw material 20, the funnel-type tool 10, and the stir portion 26a produced by the shoulderless-type tool 10, and observed the structures with a transmission electron microscope (TEM). As a result, it was found that while precipitates (Zn, Mg) were precipitated continuously and widely at the grain boundaries of the raw material 20, at the grain boundaries of the stir portion 26a produced by the funnel-type tool 10, the precipitates were merely scattered, and furthermore, almost no precipitates were observed at the grain boundaries of the stir portion 26a produced by the shoulderless-type tool 10.
[0032] Furthermore, the inventors conducted a corrosion test using a test piece made from a vertical plane parallel to the processing direction (direction of FSW processing) of the raw material 20 and the stir portion 26a by FSW processing, and a vertical plane intersecting the processing direction. As a result, many cracks several mm long were observed in the raw material 20. Almost no cracks were observed in the stir portion 26a by the funnel-type tool 10, and microcracks of about 1 mm were observed in the stir portion 26a by the shoulderless tool 10.
[0033] Furthermore, the inventors measured the hardness distribution of the stir zone and the surrounding material (base material) that were FSWed using a funnel-type tool and a shoulderless-type tool. As a result, assuming the hardness of the material 20 to be 100%, the hardness of the stir zone 26a stirred with the funnel-type tool was about 85% of that of the material 20, and the hardness of the stir zone 26a of the shoulderless-type tool 10 was about 95% of that of the material 20.
[0034] In order to improve SCC resistance (stress corrosion cracking resistance), it is necessary that the stir portion 26a, which is the peripheral portion of the treatment material 24, is finely recrystallized and that precipitates are dispersed in the grain boundaries of the fine recrystallization. Therefore, even if the stir portion 26a can be modified to be finely recrystallized, if the precipitates are not dissolved and dispersed in the grain boundaries of the fine recrystallization, the degree of improvement in SCC resistance is small.
[0035] It is very complicated and requires a lot of man-hours to confirm the degree (effect) of improvement in SCC resistance through the FSW conditions, which have many control factors such as the tool shape, tool rotation speed, and tool feed rate, and the experimental process of observing the precipitate dispersion state at the grain boundaries of the fine recrystallization in the stir portion 26a using a TEM.
[0036] Therefore, instead of confirming the SCC resistance improvement effect, which entails a large number of steps, attention is focused on the hardness, which is highly correlated with the degree of modification of the fine recrystallization of the stir portion 26a and the distribution state of precipitates precipitated at the fine recrystallized grain boundaries. The inventors have confirmed that if the hardness of the stir portion 26a, which is the peripheral portion of the treatment material 24, is within a range of 85 to 95% (predetermined hardness) of the hardness of the material 20 at the center of the treatment material 24, the SCC resistance improvement effect is achieved.
[0037] 6 is a cross-sectional view (corresponding to the cross section in FIG. 3A-A) of a material in which one stirring portion formed by inserting a tool from one surface of the material is overlapped with the other stirring portion formed by inserting a tool from the other surface. When the sheet thickness t of the material 20 is relatively small, a sufficient stirring portion 26a can be formed in the sheet thickness direction by inserting the tool 10 only from the side of one surface 20a of the material 20.
[0038] On the other hand, when the plate thickness t of the raw material 20 is large, it is difficult to form a sufficient stirring portion 26a in the thickness direction when the tool 10 is inserted only from one surface (e.g., 20a) of the raw material 20. Here, the case where the stirring portion 26a does not reach the other surface 20b is referred to as the case where the stirring portion is not formed in a predetermined range. In such a case, after the tool 10 is inserted from one surface 20a of the raw material 20 to form the stirring portion 26a, the tool 10 is also inserted from the other surface 20b of the raw material 20 to form the stirring portion 26b in a manner that overlaps the previously formed stirring portion 26a.
[0039] FIG. 7 is an oblique view of the treatment material cut along the stirring portion formed along the marking line, and FIG. 8 is a cross-sectional view of the treatment material cut along the stirring portion formed along the marking line, intersecting the marking line.
[0040] 7 and 8 explain a case where a sufficient stirring portion 26a can be formed in the thickness direction by using the tool 10 inserted from one surface 20a of the material 20. The effect is basically the same whether the stirring portions 26a, 26b are formed by inserting the tool 10 from both surfaces 20a, 20b of the material 20 or the stirring portion 26a is formed by inserting the tool 10 from one surface 20a of the material 20. For this reason, hereinafter, the case where the stirring portion 26a is formed by inserting the tool 10 from one surface 20a of the material 20 will be explained as a representative example.
[0041] The treated material 24 cut out from the raw material 20 along the marking line 22 has a pancake-like structure in its central part (raw material 20) in which crystal grains in a rolled or extruded state are arranged in layers, and its peripheral part 24a (surface along the z direction) has a stirring part 26a that has been stirred by the tool 10 and finely recrystallized.
[0042] As shown in Fig. 8, the end (peripheral portion 24a) of the treatment material 24 cut out from the material 20 at approximately the center (position of the marking line 22) in the width direction of the stir portion 26a obtained by FSWing the material 20 has the finely recrystallized stir portion 26a at all ends of the treatment material 24. The method of cutting the material 20 is, for example, but is not limited to, machining. As a result, the stir portion 26a is exposed from one surface 20a to the other surface 20b at the cut-out outer edge (peripheral portion) of the treatment material 24.
[0043] Fig. 9 is a schematic diagram showing an example in which a treatment material manufactured by the manufacturing method according to the present embodiment is welded to a fastening portion between the underframe and the yaw damper support portion of a railway car to reinforce the fastening portion, and Fig. 10 is a schematic diagram showing the treatment material welded to the railway car (an enlarged view of part A in Fig. 9). Fig. 11 is a cross-sectional view of the portion reinforced with the treatment material, intersecting with the longitudinal direction of the railway car.
[0044] 9, railway vehicle 50 is mainly composed of a hexahedral body structure on which passengers etc. ride, and bogie 70 which supports this body structure and travels along track T. The body structure is composed of underframe 52 which forms the floor surface, side body structure 51 erected at the y-direction end of underframe 52, end body structure (not shown) erected at the x-direction end of underframe 52, and a roof body structure (not shown) placed on the upper ends of side body structure 51 and the end body structure.
[0045] In FIG. 11, a side structure 51 has an exterior side panel 51a, an interior side panel 51c, and a connection portion 51b that connects these panels, and is formed from an extruded member extruded in the x direction.
[0046] The underframe 52 has side beams 53 provided continuously with the lower end of the side structure 51, a floor section (not shown) provided between one side beam 53 and the other side beam 53, end beams (not shown) provided along the y direction at both ends of the floor section in the x direction, a bolster 54 provided along the y direction at a portion located above the bogie 70, and a floor section 55. Although not shown, the side structure 51 has windows, side sliding doors through which passengers get on and off, and the like.
[0047] 9, bogie 70 includes bogie frame 71 having a generally H-shaped shape when viewed from above, axles (wheels and axles) rotatably held by bogie frame 71, and a yaw damper 72 that suppresses excessive turning movement of bogie 70 in a horizontal plane (xy plane). One longitudinal end of yaw damper 72 is connected to a side surface of bogie frame 71, and the other end is connected to a lower end of yaw damper support part 73 that is provided in a manner that hangs down from the y-direction end of bolster 54 provided on underframe 52.
[0048] When the railcar 50 travels at high speed, the bogie 70 is likely to turn in a horizontal plane due to irregularities in the track T. For this reason, a very large load may act on the upper end of the yaw damper support part 73 connected to the yaw damper 72 that suppresses the turning motion of the bogie 70 in a horizontal plane, so the upper end of the yaw damper support part 73 may be provided with a treatment material 24 as a reinforcing member.
[0049] The treatment material 24 is provided in a manner spanning the side structure 51 (car exterior side panel 51a), the side sill 53, and the bolster 54, and at least one of these portions (here, the car exterior side panel 51a) is joined to the peripheral portion 24a of the treatment material 24 via a welded portion 28. Here, the welded portion 28 is preferably formed by a method other than the FSW process, such as arc welding or gas welding (collectively referred to as non-friction stir welding). However, while FIG. 11 shows an example in which the treatment material 24 is joined to the object to be joined by welding, the method is not limited to welding, and the treatment material 24 may be joined to the object to be joined mechanically, for example, by a bolt or the like.
[0050] FIG. 12 is a flow chart showing a method for producing a treatment material according to this embodiment. First, start work with step 10. From now on, the step terms will be replaced with the notation S.
[0051] In S20, the outline of the material 24 to be treated is marked on the blank 20 with marking lines 22. This also includes the case where coordinate data of the marking lines 22 is input to, for example, a CNC machine tool.
[0052] In S30, a tool is pressed into one surface of the blank 20 under predetermined FSW conditions to form a stir portion 26a along the marking line 22 (first step).
[0053] In S40, it is determined whether the hardness of the stirring portion 26a is within a range of 85 to 95% of the hardness of the material (predetermined hardness) (fourth step). The hardness of the stirring portion 26a can be measured using a Brinell hardness test, a Vickers hardness test, a Rockwell hardness test, or the like.
[0054] If the hardness of the stirring portion 26a is within the range of 85-95% of the hardness of the material (yes), proceed to S50, and if the hardness of the stirring portion 26a is not within the range of 85-95% of the hardness of the material (no), return to S30, review the FSW conditions, and redo the FSW process. This includes the case where the material is replaced. Note that if FSW conditions that result in the hardness of the stirring portion 26a being within the range of 85-95% of the hardness of the material are obtained in advance, S40 can be omitted.
[0055] In S50, it is determined whether the stirring portions 26a formed from one surface are sufficiently distributed in the thickness direction (for example, whether they reach the other surface 20b) (third step). If it is determined in S50 that the stirring portions 26a are sufficiently distributed (yes), the process proceeds to S70, and if it is determined that the distribution is not sufficient (no), the process proceeds to S60.
[0056] In S60, the material 20 that has already been stirred is turned over, and a tool is pressed into the other surface 20b to form a stirring portion 26b along the marking line 22 in a manner that overlaps with the already stirred stirring portion 26a.
[0057] In S70, the treatment material 24 is cut out from the material 20 along the marking line (stirring portion) 22 (second step).
[0058] In S80, the treatment material 24 is positioned at a predetermined position of the object. In this embodiment, the treatment material 24 is provided so as to straddle the side structure 51 (the outer side panel 51a of the vehicle) as the object, the side sill 53, and the bolster 54.
[0059] In S90, the positioned treatment material 24 is joined to a predetermined position of the target object by welding, mechanical fastening, etc. In the present embodiment, as an example, a welded portion 28 is formed across the stirring portion 26a of the treatment material 24 and the vehicle exterior side panel 51a.
[0060] Finish the work with S100.
[0061] <Effects> After forming the stir portion 26a (26b) in the raw material 20, the material to be treated 24 is cut out from the raw material 20 along the stir portion 26a (26b), so that the peripheral portion 24a of the material to be treated has a structure that has been finely recrystallized by the FSW process. Therefore, there is no need to take measures against stress corrosion cracking, which require a relatively large number of steps, such as peening to remove tensile stress from the end (end face) of the peripheral portion 24a of the material to be treated 24 or buttering welding to the end face of the material to be treated 24, so a method for manufacturing a material to be treated made of a high-strength aluminum alloy that can increase resistance to stress corrosion cracking with a small number of steps can be provided.
[0062] Furthermore, the degree (effect) of improvement in SCC resistance is evaluated based on the degree of modification of fine recrystallization in the stir portion 26a, instead of the FSW conditions with many control factors and the experimental process of observing the stir portion 26a with a TEM. Also, focusing on the degree of modification of fine recrystallization in the stir portion 26a and the hardness, which is highly correlated with the distribution state of precipitates precipitated at the refined recrystallized grain boundaries, it can be evaluated that the stir portion 26a has an effect of improving SCC resistance if the hardness of the stir portion 26a is in the range of 85 to 95% of the hardness of the material 20. Therefore, by performing the FSW process until the hardness of the stir portion 26a becomes 85 to 95% of the hardness of the material, it is possible to provide a manufacturing method for a treated material made of a high-strength aluminum alloy that can increase the resistance to stress corrosion cracking with a small number of steps.
[0063] Furthermore, after inserting the tool 10 from one side of the material 20 to form the stirring portion 26a, a step of forming the stirring portion 26b from the other side of the material 20 is added as necessary by determining whether the formed stirring portion 26a is sufficient in the thickness direction of the material 20, so that a treated material 24 having a sufficiently finely recrystallized stirring portion 26a (26b) can be obtained. Therefore, since there is no need to take measures against stress corrosion cracking that require a relatively large number of steps as described above, a method for manufacturing a treated material made of a high-strength aluminum alloy that can increase resistance to stress corrosion cracking with a small number of steps can be provided.
[0064] Furthermore, when the peripheral portion 24a of the treatment material 24 is welded to an object to be joined, the peripheral portion 24a is stirred by the tool 10 to improve the material quality and has a finely recrystallized structure with SCC resistance. Therefore, even if the welded peripheral portion 24a is cooled after welding the peripheral portion 24a of the treatment material 24 and tensile residual stress occurs, there is no need to take measures against stress corrosion cracking that require a relatively large number of steps, so it is possible to provide a method for manufacturing a treatment material made of a high-strength aluminum alloy that can increase resistance to stress corrosion cracking with a small number of steps.
[0065] Furthermore, according to this embodiment, the structure of the peripheral portion 24a of the material 24 cut out from the raw material 20, where stress corrosion cracking is likely to occur, can be refined by FSW treatment instead of heat treatment. In general, when the peripheral portion 24a of the raw material 20, which has a high thermal conductivity, is heated to a temperature required for heat treatment, heat is conducted not only to the peripheral portion 24a to be heated but also to a portion that does not need to be heated (for example, the center portion of the raw material 20) by thermal conduction, so a large heating energy is required. According to this embodiment, the material 20, which is prone to stress corrosion cracking, is locally FSW-treated with small energy consumption, and then cut out along the FSW-treated processed portion. Therefore, the peripheral portion 24a, which is finely recrystallized and has high SCC resistance, is exposed on the end face of the material 24 (the vertical surface intersecting (and parallel to) the rolling direction), so that a method for manufacturing a high-strength aluminum alloy material that can increase resistance to stress corrosion cracking with a small number of steps can be provided.
[0066] This specification includes the disclosure of the following inventions. (First aspect) In the method for producing a treatment material, A first step of performing friction stirring processing on a material to form a stirring portion; A second step of cutting out a treatment material from the material along the stirring portion; having A method for producing a treatment material, comprising the steps of:
[0067] (Second aspect) In the method for producing a treatment material according to the first aspect, a third step of determining whether the stir portion is formed to a predetermined range in the thickness direction of the material, and when it is determined that the stir portion is not formed to the predetermined range, performing friction stir treatment from the other surface opposite to the one surface that has been subjected to the friction stir treatment in the first step toward the one surface to form a stir portion; A method for producing a treatment material, comprising the steps of:
[0068] (Third aspect) In the method for producing a treatment material according to the first or second aspect, A fourth step of determining whether the hardness of the stirring portion is a predetermined hardness or not, and executing the second step when it is determined that the hardness is the predetermined hardness; A method for producing a treatment material, comprising the steps of:
[0069] (Fourth aspect) In the treatment material produced by the production method according to any one of the first to third aspects, The stirring portion, which is a fine recrystallized structure, is exposed at the outer edge portion cut out in the second step of the treatment material; A treatment material characterized by:
[0070] (Fifth aspect) In the treatment material of the fourth aspect, The stirring portion and other parts are welded together; A treatment material characterized by:
[0071] (Sixth aspect) In the treatment material according to the fourth or fifth aspect, The material is a 7000 series aluminum alloy. A treatment material characterized by:
[0072] (Seventh aspect) A treatment material having a central portion and a peripheral portion continuous with the central portion, the treatment material being made of the same material, The central portion has a structure in which crystal grains are arranged in layers, the structure of the peripheral portion is more finely recrystallized than the structure of the central portion; The finely crystallized structure is exposed at the outer edge of the treatment material; A treatment material characterized by:
[0073] (Eighth aspect) In the seventh aspect of the treatment material, The treatment material is a 7000 series aluminum alloy; A treatment material characterized by:
[0074] (Ninth aspect) In the treatment material according to the seventh to eighth aspects, the hardness of the peripheral portion is in the range of 85 to 95% of the hardness of the central portion; A treatment material characterized by:
[0075] (Tenth Aspect) In the treatment material according to any one of the seventh to ninth aspects, The treatment material is provided in a manner spanning a side structure, a side beam, and a bolster of a railway vehicle, and a peripheral portion of the treatment material is joined to at least one of the side structure, the side beam, and the bolster via a welded portion; A treatment material characterized by: [Explanation of symbols]
[0076] 10...tool, 10a...large diameter portion, 10b...small diameter portion, 10c...shoulder portion, 20…Material, 20a...one side (material), 20b...other side (material), 22... marking line, 24... processing material (reinforcing material), 24a...periphery, 26a...stirring portion (one surface), 26b...stirring portion (other surface), 28...welding portion, 50...Railway vehicle, 51...Side structure (side beam), 51a...Vehicle outer side plate, 51b...Connection part, 51c...interior side panel, 52...frame, 53...side beam, 54...pillar beam, 55...Floor section, 70...Cart, 71... bogie frame (side beam), 72... yaw damper, 73... Yaw damper support portion, 100... Rotation direction, 101...vertical movement direction, 102...tool movement path (stroke), T...trajectory, t...thickness, x...rail (longitudinal) direction, y...sleeper (width) direction, z: Height direction
Claims
1. In the method for producing a treatment material, A first step of subjecting a material to a friction stirring process to form a stirring portion; A second step of cutting out a treatment material from the material along the stirring portion; having A method for producing a treatment material, comprising the steps of:
2. In the method for producing the treatment material according to claim 1, a third step of determining whether the stir portion is formed to a predetermined range in the thickness direction of the material, and when it is determined that the stir portion is not formed to the predetermined range, performing friction stir treatment from the other surface opposite to the one surface that has been subjected to the friction stir treatment in the first step toward the one surface to form a stir portion; A method for producing a treatment material, comprising the steps of:
3. In the method for producing the treatment material according to claim 1, A fourth step of determining whether the hardness of the stirring portion is a predetermined hardness or not, and executing the second step when it is determined that the hardness is the predetermined hardness; A method for producing a treatment material, comprising the steps of:
4. A treatment material produced by the method according to claim 1, The stirring portion, which is a fine recrystallized structure, is exposed at the outer edge portion cut out in the second step of the treatment material; A treatment material characterized by:
5. The treatment material according to claim 4, The stirring portion and other parts are welded together; A treatment material characterized by:
6. The treatment material according to claim 5, The material is a 7000 series aluminum alloy. A treatment material characterized by:
7. A treatment material having a central portion and a peripheral portion continuous with the central portion, the treatment material being made of the same material, The central portion has a structure in which crystal grains are arranged in layers, the structure of the peripheral portion is more finely recrystallized than the structure of the central portion; The finely crystallized structure is exposed at the outer edge of the treatment material; A treatment material characterized by:
8. The treatment material according to claim 7, The treatment material is a 7000 series aluminum alloy; A treatment material characterized by:
9. The treatment material according to claim 8, the hardness of the peripheral portion is in the range of 85 to 95% of the hardness of the central portion; A treatment material characterized by:
10. The treatment material according to claim 7, The treatment material is provided in a manner spanning a side structure, a side beam, and a bolster of a railway vehicle, and a peripheral portion of the treatment material is joined to at least one of the side structure, the side beam, and the bolster via a welded portion; A treatment material characterized by:
Citation Information
Patent Citations
Friction stirring joining method
JP1999090655A